The CORRELATION BETWEEN URINE ALBUMIN-CREATININE RATIO WITH BACTERIURIA - Yusianti Silviani; Rochmad Hidayah Romadhon (LPPM Universitas Abdurrab, 2025)
Chronic kidney disease in patients results from the colonization of the periurethral area by gastrointestinal bacterial flora resulting in colonization of the urethra. Pathogens then migrate to the bladder, express fimbriae and adhesins, and cause colonization and invasion of bladder umbrella cells. The immune system then activates an inflammatory response with neutrophil infiltration to eradicate the bacteria. Bacteria that survive through the immune system produce toxins and proteases that damage host cells. The bacteria then provide essential nutrients for defense. The bacteria then begin to move to the kidneys, once colonized in the kidneys, the bacteria can release toxins that damage kidney cells in the host. The infection then penetrates the renal tubular epithelial barrier causing bacteriuria and kidney damage. The purpose of this study was to determine whether there is a relationship or correlation of urine albumin creatinine results to bacteriuria. This research method is observational analytic. The sampling technique used was Quota sampling using 44 respondents who did not take antibiotics for 1 week and did not use a catheter. Bacteriuria was examined using microscopic examination method with malbin staining. Data analysis using the chi-square test, based on the results of the comparison between the results of the urine albumin creatinine ratio to bacteriuria, the results obtained p = 0.000 (p < 0.05). The conclusion of this study is that there is a relationship between the results of urine albumin creatinine ratio to bacteriuria.